Impact of clustered failures on connectivity of wireless sensor networks - Arifler, Do?u (My University, 2008)
Wireless sensor networks have extensive applications in monitoring ambient conditions of critical infrastructure and natural resources. Natural or artificial hazards, such as fires or any other form of systematic destructions by adversaries, may destroy a large number of close-proximity sensors, compromise network connectivity, and hence disrupt proper reporting of measurements of interest to a "sink." Our previous work has shown that as few as approximately 20 close-proximity sensor failures in dense networks could be considered "unusual" enough to infer with 90% confidence that a hazard is occurring, and this is independent of deployment density. In this paper, an evaluation of the impact of systematic node destructions on the connectivity of low RF-power wireless sensor networks is presented. Simulation results demonstrate that with typical sensor RF-transceiver power settings and an initially connected deployment, more than 98% of sensors remain connected to the sink when a cluster of 20 sensors fail in completely randomly deployed sensor networks. This observation is significant since monitoring systems must be able to detect occurrence of hazards before network connectivity is compromised. ©2008 by Bo?aziçi University.
8th International Symposium on Computer Networks, ISCN'08 --
Keywords: Computer networks; Computers; Hybrid sensors; Internet; Metropolitan area networks; Proximity sensors; Sensor networks; Sensors; Ambient conditions; Critical infrastructures; Dense networks; Monitoring systems; Network connectivities; OF sensors; Power settings; Randomly deployed; Simulation results; Wireless sensor networks